Glycan repositioning of influenza hemagglutinin stem facilitates the elicitation of protective cross-group antibody responses - Seyhan Boyoglu-Barnum (Nature Portfolio, 2020)
Influenza virus hemagglutinin (HA) stem between group 1 and 2 viruses has different glycosylation patterns, likely hampering cross-group protection. Here, Boyoglu-Barnum et al. show that introducing a group 2 glycan into a group 1 stem nanoparticle vaccine broadens antibody responses in mice to cross-react with group 2 HAs.